Rational Expectations, Informational Efficiency, and Tests Using Survey Data: A Reply - Figlewski, Stephen; Wachtel, Paul (The Review of Economics and Statistics, 1983)
even if it does not eliminate them completely. The primary effect of using individual expectations data rather than cross-sectional averages as a regressor is to introduce additional measurement error. Finally, the distinction between expectations and full informational efficiency is more than a semantic one. The failure to make this distinction seems to be the cause of substantial confusion in the literature. The distinction has become increasingly important with the advent of expectations macroeconomic models (see Lucas, 1973; Barro, 1976) which are driven by imperfections and asymmetries of information, yet in which each economic agent is assumed to process rationally the information he possesses. In particular, empirical tests which depend upon full informational efficiency can provide little evidence on the validity of the rational expectations hypothesis as that term has come to be used in macroeconomics.